2012
DOI: 10.1111/j.1365-3059.2012.02677.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cucurbits in the epidemiology of Papaya ringspot virus type P

Abstract: Papaya ringspot virus type P (PRSV-P) systemically infects Carica papaya and species belonging to the family Cucurbitaceae. Attempts to recover PRSV-P from naturally infected cucurbit plants grown near or among diseased papaya trees have shown conflicting results worldwide. This study aimed to evaluate the natural infection of cucurbit species grown among and near papaya trees infected with PRSV-P in Brazil. Natural infection of cucurbits with PRSV-P occurred in zucchini squash but not in watermelon and cucumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
0
15
0
2
Order By: Relevance
“…These practices include the following: the use of virus-free seedlings for new plantings; the eradication of old and abandoned orchards before starting new crops; the avoidance of cucurbit plants, which may harbour the virus within the proximity of the orchard; and, in particular, the roguing of diseased plants by means of systematic inspections of the crops by well-trained personnel (Ventura et al, 2004). Although growers are recommended to avoid the planting of cucurbit plants within or near the orchard, recent studies conducted in Brazil by Mansilla et al (2013) revealed that these species do not have a significant importance on the epidemiology of papaya ringspot disease. The control of PRSV-W and ZYMV relies mainly on the use of resistant/tolerant cucurbit varieties whenever available.…”
mentioning
confidence: 99%
“…These practices include the following: the use of virus-free seedlings for new plantings; the eradication of old and abandoned orchards before starting new crops; the avoidance of cucurbit plants, which may harbour the virus within the proximity of the orchard; and, in particular, the roguing of diseased plants by means of systematic inspections of the crops by well-trained personnel (Ventura et al, 2004). Although growers are recommended to avoid the planting of cucurbit plants within or near the orchard, recent studies conducted in Brazil by Mansilla et al (2013) revealed that these species do not have a significant importance on the epidemiology of papaya ringspot disease. The control of PRSV-W and ZYMV relies mainly on the use of resistant/tolerant cucurbit varieties whenever available.…”
mentioning
confidence: 99%
“…Mexican Journal oF PhytoPatholoGy fuera de cultivos de papayo infectados con PRSV-P utilizando ELISA y RT-PCR (Mansilla et al, 2013). En Florida, se reportó la presencia de PRSV-W en especies vegetales de la familia Cucurbitaceae, afectando los cultivos de pepino, calabaza, melón y sandía; también se detectó como hospedante de maleza, entre las cuales están Momordica balsamina, Melothria pendula y Coccinia grandis (Goyal et al, 2012;Tantiwanich et al, 2014).…”
Section: Fully Bilingual Revista Mexicana De Fitopatologíaunclassified
“…La detección de PRSV mediante DAS-ELISA y RT-PCR en plantas de C. papaya y maleza asociada extensively reported as hosts for PRSV (NoaCarranza et al, 2006;Sreenivasulu and SaiGopal, 2010;Goyal et al, 2012;Mansilla et al, 2013). Phylogenetics (Figure 3) was useful to identify three similar sequence groups.…”
Section: Detección De Prsvmentioning
confidence: 99%
See 2 more Smart Citations